1995
DOI: 10.1007/bf00187775
|View full text |Cite
|
Sign up to set email alerts
|

Lower-extremity venous stasis during laparoscopic cholecystectomy as assessed using color Doppler ultrasound

Abstract: Lower-extremity venous stasis during laparoscopic cholecystectomy was evaluated in 16 patients by monitoring the blood velocity in the femoral vein and the femoral vein size (cross-sectional area) using color Doppler ultrasonography. The blood velocity in the femoral vein decreased significantly after the start of 10-mmHg abdominal insufflation in the supine position. When the patients were placed in a reverse Trendelenburg position during 10-mmHg insufflation, blood velocity in the femoral vein further decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
25
0
1

Year Published

1998
1998
2007
2007

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 15 publications
1
25
0
1
Order By: Relevance
“…In our study, use of the reverse Trendelenburg position during open GBP decreased femoral peak systolic velocity by 38%, whereas reverse Trendelenburg position with pneumoperitoneum during laparoscopic GBP reduced femoral peak systolic velocity by 57% of the baseline value as compared with a 43% reduction in femoral peak systolic velocity during pneumoperitoneum alone. Our findings are in keeping with the observations of other investigators who demonstrated that combining the reverse Trendelenburg position with pneumoperitoneum has an additive effect and decreases femoral peak systolic velocity by 42-61% [4,7].…”
Section: Discussionsupporting
confidence: 95%
See 4 more Smart Citations
“…In our study, use of the reverse Trendelenburg position during open GBP decreased femoral peak systolic velocity by 38%, whereas reverse Trendelenburg position with pneumoperitoneum during laparoscopic GBP reduced femoral peak systolic velocity by 57% of the baseline value as compared with a 43% reduction in femoral peak systolic velocity during pneumoperitoneum alone. Our findings are in keeping with the observations of other investigators who demonstrated that combining the reverse Trendelenburg position with pneumoperitoneum has an additive effect and decreases femoral peak systolic velocity by 42-61% [4,7].…”
Section: Discussionsupporting
confidence: 95%
“…Pneumoperitoneum during laparoscopy clearly has been shown to induce venous stasis by reducing femoral peak systolic velocity [1,2,4], increasing femoral venous pressure [2], and reducing femoral venous flow [9]. Beebe et al [2] reported that abdominal insufflation to 14 mmHg decreased femoral peak systolic velocity by 26% and increased femoral venous pressure by 78%; deflation of the abdomen lowered femoral venous pressure and returned femoral peak systolic velocity to baseline levels.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations